Kajian pustaka toksisitas tanaman nanas (Ananas comosus [L.] Merr) - Qurratul Aeni; Siti Rahmatul Aini; Iman Surya Pratama (Universitas Mataram, 2022)
Pineapple plants are used ethnomedicinally in various countries, especially in Indonesia. Several studies have shown that pineapple plants have pharmacological effects both in vitro and in vivo on various diseases. Ananas Plant has the potential to be cultivated as medicine products. The toxicity of Ananas comosus (L) Merr important to acknowledge. This literature review aims to provide comprehensive information through a literature review regarding the toxicity of pineapple (Ananas comosus [L.] Merr). The literature review was collected in the period 2010 to 2021 which was obtained from the Google Scholar and Pubmed databases with a total of 9544 and a study was carried out on 10 works of literature. Based on the results of 10 literatures that have met the inclusion criteria, it shows that the in vitro toxicity test on pineapple (Ananas comosus [L.] Merr) has an LC50 of 403.83 to 9000 ppm which belongs to the category of practically non-toxic to moderately toxic. In vivo toxicity test showed that LD50 > 5000 mg/kgBW showed no deaths which were classified as practically non-toxic. From the results of literature research, it can be said that toxic plants (Ananas comosus [L.] Merr) have a toxicity category of practically non-toxic to moderately toxic in vitro studies. The results of the in vivo test showed that there were no deaths in the test animals which were in the category of practically non-toxic to mildly toxic.